Early Stunting Prevention: Community Empowerment Through Oral Health Promotion for Prospective Brides and Pregnant Women - Handayani, Rika; Sudarmin, Ria Rezeki; Saeni, Rahmat Haji (Sarana Ilmu Indonesia (salnesia), 2025)
Oral health is an essential component of overall health, particularly for pregnant women and prospective brides. Nevertheless, knowledge and awareness regarding oral health remain low, contributing to the high prevalence of dental caries, gingivitis, and periodontitis. These conditions have serious implications, especially during the First 1000 Days of Life (HPK), which are closely associated with the risk of stunting. This program aimed to enhance knowledge, awareness, and preventive behaviors related to oral health among pregnant women and prospective brides as part of early stunting prevention efforts. The intervention was conducted in July 2023 at the Toddopuli Primary Health Center, Makassar City, involving 20 prospective brides, 30 pregnant women, and 10 health cadres. Activities included cross-sectoral coordination, technical training for health cadres, household visits for data collection and intervention sticker placement, oral health education through face-to-face counseling and digital media, and dental treatment at the health center. Knowledge was assessed using pre-test and post-test instruments administered via Google Form. The findings revealed a significant improvement: the proportion of participants with good knowledge increased from 49,2% before the intervention to 98,2% afterward. In addition, the number of participants receiving dental care rose from 4 in 2022 to 39 in 2023. Overall, the program successfully enhanced awareness and preventive practices and contributed to stunting prevention by improving maternal and preconception oral health.